SEMINAR-STYLE CLASSES IN THE SYSTEM OF POSTGRADUATE DENTAL EDUCATION - Sheshukov, A. (World of Medicine and Biology, 2014)
The paper consideres the role of seminar-style classes in postgraduate dental education. Organizational and didactic principles have been analysed, which are the basis for structuring of a seminar. It is shown that application of specified principles in making seminars for interns in Children’s Dentistry allows solving the problem of highly skilled specialists’ training, acquiring deep knowledge in major subject and allied disciplines.
Keywords: postgraduate education; dentist; seminar-style classes